A Rechargeable Battery with an Iron Metal Anode. (28th March 2019) - Wu, Xianyong; Markir, Aaron; Xu, Yunkai; Zhang, Chong; Leonard, Daniel P.; Shin, Woochul; Ji, Xiulei
Abstract: To date, tremendous efforts of the battery community are devoted to batteries that employ Li +, Na +, and K + as charge carriers and nonaqueous electrolytes. However, aqueous batteries hold great promise for stationary energy storage due to their inherent low cost and high safety. Among metal batteries that use aqueous electrolytes, zinc metal batteries are the focus of attention. In this study, iron as an anode candidate in aqueous batteries is investigated because iron is undoubtedly the most earth‐abundant and cost‐effective metal anode. Reversible iron plating/stripping in a FeSO4 electrolyte is demonstrated on the anode side and reversible topotactic (de)insertion of Fe 2+ in a Prussian blue analogue cathode is showcased. Furthermore, it is revealed that LiFePO4 can pair up with the iron metal anode in a hybrid cell, delivering stable performance as well. Abstract : The plating/stripping reversibility of an iron metal anode is demonstrated, which can pair with a Fe‐based Prussian blue as the cathode in a full‐cell configuration with a FeSO4 solution as the electrolyte. The iron metal anode can couple with the LiFePO4 cathode to form an aqueous hybrid battery as well.